2004
DOI: 10.1099/vir.0.80296-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tombusvirus open reading frames 1 and 2 is sufficient for the replication of defective interfering, but not satellite, RNA

Abstract: Yeast cells co-expressing the replication proteins p36 and p95 of Carnation Italian ringspot virus (CIRV) support the RNA-dependent replication of several defective interfering (DI) RNAs derived from either the genome of CIRV or the related Cymbidium ringspot virus (CymRSV), but not the replication of a satellite RNA (sat RNA) originally associated with CymRSV. DI, but not sat RNA, was replicated in yeast cells co-expressing both DI and sat RNA. Using transgenic Nicotiana benthamiana plants constitutively expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
(71 reference statements)
2
8
0
Order By: Relevance
“…These proteins were expressed either by two separate plasmids (lane 4) or by only one plasmid expressing wt p92 (lane 3), whereas no progeny RNA was detected when p92 (lane 1) or p33 (lane 2) were omitted. As in previous experiments (Pantaleo et al, 2004;Rubino et al, 2004;Navarro et al, 2006), the progeny DI RNA was composed of monomers and dimers (Fig. 7a, lanes 3 and 4).…”
Section: Rna Replication and Localization Of The Replication Complsupporting
confidence: 83%
See 1 more Smart Citation
“…These proteins were expressed either by two separate plasmids (lane 4) or by only one plasmid expressing wt p92 (lane 3), whereas no progeny RNA was detected when p92 (lane 1) or p33 (lane 2) were omitted. As in previous experiments (Pantaleo et al, 2004;Rubino et al, 2004;Navarro et al, 2006), the progeny DI RNA was composed of monomers and dimers (Fig. 7a, lanes 3 and 4).…”
Section: Rna Replication and Localization Of The Replication Complsupporting
confidence: 83%
“…Only cells expressing both p33 and p92 would be able to replicate DI-3/MS2, switching the localization of GFP from the nucleus to the site of DI RNA replication. Transformed yeasts were grown as described previously (Pantaleo et al, 2003;Rubino et al, 2004) and divided in two aliquots, from one of which RNA was extracted and the other was fixed for immunofluorescence analysis. Northern blot analysis of RNA extracts showed that mutant DI RNA molecules containing the MS2 recognition sequence in both positive (Fig.…”
Section: Rna Replication and Localization Of The Replication Complmentioning
confidence: 99%
“…The primary structure of satRNA L was more similar to that of CymRSV satRNA than TBSV B1 and B10 satRNAs, particularly in the 59-terminal 60 nt and in the 39-terminal 4 nt, where the triplet CCC was preceded by an A instead of a G. The presence of a G at position 24 is an absolute requirement for the replication of tombusvirus genomic and DI RNAs and it may represent the position of initiation of minus-strand Characteristics of a TBSV satellite RNA synthesis (Dalmay et al, 1993b;Havelda & Burgyán, 1995;Pantaleo et al, 2003). By analogy with experimental evidence gained for CymRSV satRNA, a similar replication strategy for satRNA L can be suggested, where the concurrent replication of genomic RNA is required rather than the sole expression of the replicase proteins, which is sufficient to replicate DI RNAs (Kollar & Burgyán, 1994;Rubino et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rubino et al [77] demonstrated that co-expressing the replication proteins of Carnation Italian ringspot virus (CIRV) in yeast cells could support the replication of several defective interfering RNAs derived from the genome of CIRV or the related CymRSV but not that of a satRNA originally associated with CymRSV. Taken together, the results suggest that satRNAs have adopted a system similar to but distinct from their cognate helper viruses for their replication and thus are not strong competitors of their helper viruses.…”
Section: Recent Advances Regarding Satrnasmentioning
confidence: 99%